Relación entre work-life balance y satisfacción laboral en trabajadores en modalidad remota - Salazar Dávila, Claudia Daniela (2024)
The objective of this applied review was to identify the relationship between work-life balance and job satisfaction in remote workers. A systematic research was carried out in various research articles taking into consideration the guidelines of PRISMA (Page et al., 2021. The databases consulted were Scopus, Ebsco and PubPysch, where 10 investigations published between 2020 and 2023 were reviewed in detail. The results show that there is a positive relationship between work-life balance and job satisfacción in remote workers. Although most studies show this relationship, there is little scientific evidence between both variables, which is why future research is encouraged to focus on developing theoretical models on work-life balance and encouraging labor policies in order to improve satisfaction. from the workers.